Chitinase-3-Like Protein 1 (YKL-40) Is a New Biomarker of Inflammation in Psoriasis - Joanna Salomon (Mediators of Inflammation, 2017)
Purpose. The evaluation of new inflammatory biomarkers in psoriasis could determine therapeutic decisions. Chitinase-3-like protein 1 (YKL-40) plays a role in inflammation. The study was undertaken to check whether YKL-40 is a reliable biomarker of inflammation in psoriasis. Materials and Methods. 55 psoriatic patients were enrolled, including 21 men and 34 women, aged from 18 to 88 years. The PASI and body surface area were calculated for all patients. Blood samples were taken to evaluate serum concentration of YKL-40, as well as other inflammatory parameters, including CRP, ESR, white blood cell count, and neutrophil count. The measurements of YKL-40 level were performed by enzyme-linked immunosorbent assay (ELISA). Results. YKL-40 serum concentration was significantly higher in psoriatic patients than in the control group. No correlations were found between YKL-40 levels and other clinical or laboratory parameters. Serum YKL-40 level was elevated in 81.8% patients, whereas CRP and WBC in 20% and 7.3% of patients, respectively. Conclusions. YKL-40 could be considered as a useful biomarker of inflammation in psoriasis and is more sensitive than CRP or WBC. Increased YKL-40 may indicate psoriatic patients with a higher level of systemic inflammation, which may determine disease management.